Transgression and Deviance in the Ancient World - Gilhaus, Lennart; Dorn, Anja.; Herrad, Imogen; Meurer, Michael (Stuttgart : J.B. Metzler : Imprint: Palgrave Macmillan, 2022)
Social coexistence is made possible and regulated by norms. Which actions are labeled and sanctioned as transgressions of norms is the result of social negotiation processes. Transgression and norm deviance can both stabilize and undermine the existing norm system. The contributions to this anthology aim to provide some impulses on the relationship between norm and deviance in ancient societies by means of selected case studies from the Greek classical period to the Roman imperial period and to investigate the role of transgressive acts for the dynamics of social systems. This book is a translation of an original German edition. The translation was done with the help of artificial intelligence (machine translation by the service DeepL.com). A subsequent human revision was done primarily in terms of content, so that the book will read stylistically differently from a conventional translation.
The representation of norm transgressions and deviant behavior in ancient societies - An introduction -- The tragedian Agathon in Aristophanes and Plato. The dramatic construction of deviant behavior -- Transformation or transgression? Initiation and transition rituals in the Attic cult of Artemis -- Just reward - just punishment? Religious norms, norm transgressions and their consequences in Xenophon's Hellenika -- When is Revolt not Revolting? Rule-breaking and Revolt in Sparta in Plutarch's Lives -- Sanguine non modo se non contaminarunt, sed etiam honestarunt -- Transgressions in Lucan - A necessary evil? -- Dux femina - Transgressive women in Tacitus -- Aesthetic transgressions in ancient art using the example of painted sculptures.
Keywords: History; History, Ancient; Civilization-History.; Social history; Classical literature; Literature, Ancient; History; Classical Studies; Cultural History; Social History; Classical and Antique Literature